0250 Occupational exposure and stroke - A critical review of chemical and physical exposures. (23rd June 2014) - Gustavsson, Per; Jakobsson, Kristina
Abstract : Objectives: Stroke is the third most common cause of death in developed countries, exceeded only by coronary heart disease and cancer. There is substantial scientific literature on the association between occupational exposures and coronary heart disease, but much less is known about stroke. This systematic critical review was performed to assess the strength of evidence for causal associations between chemical and physical occupational exposures and stroke. Method: Literature on stroke incidence or mortality and occupational factors published up to 2012 was identified from Medline and Scopus. The 4 471 abstracts were evaluated independently by two reviewers. 29 studies relevant to chemical and physical exposures were identified; ionising irradiation (7 studies); carbon disulfide (4), dynamite (3), motor exhaust (7) and other combustions products (8). The evidence for an association was assessed according to defined criteria as strong, moderate, limited, or insufficient. Results: There is strong evidence for an association between high exposure to ionising irradiation and stroke, from studies on patients undergoing therapeutic x-tray treatment and atomic bomb survivors. The evidence for an association with occupational exposure to ionising irradiation is limited. There is moderate evidence for an increased risk among smelter workers, and limited evidence for carbon disulfide. The evidence for dynamite, motor exhaust and other combustion products is insufficient. Conclusions: This review identified limited evidence for an association between several chemical and physical occupational exposures and stroke. The few available studies on smelter workers all showed indications of an increased risk of stroke, and this association needs further investigation.